Caracterización bromatológica y sensorial del licor de cacao de tres variedades tras el proceso de fermentación alcohólica-acética con saccharomyces cerevisiae - Carrillo Romero, Danny Manuel; Malla Illescas, Joel Antonio (Machala: Universidad Técnica de Machala, 2024)
In the present study, the effect of the cocoa variety on the bromatological and sensory characteristics of three varieties of liquor was investigated: national, trinitario and forastero, carrying out an evaluation of the chemical characteristics of the mucilage and almond (pH, soluble solids, polyphenols) during the fermentation process with the addition of Saccharomyces cerevisiae yeast. Bromatological analysis evaluated parameters of fiber, ash, fat, protein and moisture content. On the other hand, sensory analysis focused on the characterization of the flavor and aroma profile of the cocoa liquor, in addition to evaluating the preference between the samples. Through statistical analysis, the existence of significant differences (p <0.05) was determined both for the bromatological characteristics and the global acceptance of the cocoa liquor, applying one- and two-factor ANOVA variance analysis and Tukey's post hoc test. The results obtained showed that, during the fermentation of the cocoa bean, the levels of pH, soluble solids and polyphenols had a typical drop in fermentation processes of this type, achieving stability and favoring the production of chemical components necessary for the elaboration of cocoa derived products. The statistical analysis carried out determined that there are significant differences between the groups for all bromatological parameters. However, for the overall acceptance, no significant difference was found, obtaining values of p>0.05 for both the variety studied and for the acceptance of the panelist. The study concluded that the bromatological characteristics of the cocoa liquor are influenced by its variety, while, for the overall preference, the taster's experience is a determining factor to avoid false positives. However, the tabulated analysis shows that the National variety was the most accepted.
En el presente estudio se investigó el efecto de la variedad de cacao sobre las características bromatológicas y sensoriales de licor de tres variedades: nacional, trinitario y forastero, realizando una evaluación de las características químicas al mucilago y almendra (pH, solidos solubles, polifenoles) durante el proceso fermentativo con adición de levadura Saccharomyces cerevisiae, análisis bromatológicos evaluaron parámetros del contenido de fibra, cenizas, grasa, proteína y humedad. Por otro lado, los análisis sensoriales se centraron en la caracterización del perfil de sabor y aroma al licor de cacao, además de evaluar la preferencia entre las muestras. Mediante análisis estadístico se determinó la existencia de diferencias significativas (p<0,05) tanto para las características bromatológicas y la aceptación global del licor de cacao, aplicando análisis de varianza ANOVA de uno y dos factores y prueba de post hoc de Tukey. Los resultados obtenidos mostraron que, durante la fermentación de la almendra de cacao los niveles de pH, solidos solubles y polifenoles tuvieron una caída típica en procesos fermentativos de este tipo, logrando una estabilidad y favoreciendo a la producción de componentes químicos necesarios para la elaboración de productos derivados del cacao. Los análisis estadísticos realizados determinaron que existen diferencias significativas entre los grupos de todos los parámetros bromatológicos. No obstante, para la aceptación global no se encontró una diferencia significativa obteniendo valores de p>0,05 tanto para la variedad estudiada como para la aceptación del panelista. Concluyendo en el estudio que las características bromatológicas del licor de cacao están influenciadas por su variedad, mientras que, para la preferencia global, la experiencia del catador es un factor determinante para evitar falsos positivos. Sin embargo, el análisis tabulado muestra que la variedad Nacional fue la más aceptada.
Keywords: CACAO; NACIONAL; TRINITARIO; FORASTERO